NILAI -NILAI EDUKASI DALAM KITAB 'SULUK WUJIL' KARYA SUNAN BONANG - Arti Maraya; Dadan Rusmana (Universitas Muhammadiyah Ponorogo, 2022)
The aim of this article is to analyze the meaning of the book Suluk Wujil by Sunan Bonang, one of the Nine Wali Songo. Suluk Wujil is one of the greatest literary heritages in Indonesia. The method used is literature study. The analysis of Suluk Wujil itself will be discussed more deeply in this article, there are many educational values that can be taken in this Suluk Wujil book such as the values of responsibility, loyalty, religion, divinity and many more. Sunan Bonang is one of the Wali Songo who plays a very important role in the spread of Islamic literature in Indonesia with his major works, one of which is Suluk Wujil.